Predicting the effect of treatment in paediatric OSA by clinical examination and functional respiratory imaging. Issue 6 (7th March 2017) - Slaats, Monique; Vos, Wim; Van Holsbeke, Cedric; De Backer, Jan; Loterman, Dieter; De Backer, Wilfried; Boudewyns, An; Verhulst, Stijn
Abstract: OBJECTIVE: The aim of this study was to investigate whether functional respiratory imaging (FRI) or clinical examination could predict treatment outcome for obstructive sleep apnea (OSA) in normal‐weight, non‐syndromic children. METHODS: Normal weight children diagnosed with OSA by polysomnography were prospectively included. All children got a thorough evaluation and an ultra‐low dose computed tomography scan of the upper airway (UA). A 3‐D reconstruction was built combined with computational fluid dynamics for FRI. Decisions on the need and type of surgery were based upon findings during drug‐induced sleep endoscopy. A second polysomnography was performed 3‐12 months after surgery. RESULTS: Ninety‐one children were included: 62 boys, 5.0 ± 2.7 years, and BMI z‐score of −0.1 ± 1.2. Children with more severe OSA had a smaller volume of the overlap region between the adenoids and tonsils. Nineteen out of 60 patients had persistent OSA (oAHI >2/h). A lower conductance in the UA and a higher tonsil score predicted successful treatment. CONCLUSIONS: A less constricted airway, as characterized by both FRI and a lower tonsil score, was associated with a less favorable response to (adeno) tonsillectomy. Further studies after treatment using FRI and DISE are warranted to further characterize the UA of these subjects.